KEEFEKTIFAN PENGGUNAAN MEDIA "TREE COUPLE" TERHADAP HASIL BELAJAR TEMA LINGKUNGAN SISWA KELAS II SD N MULYOHARJO 01 JEPARA - Aries Tika Damayani; Fajar Intan Pradina (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2013)
This research is motivated by the low learning results obtained by students in the Mathematics and Civics Lessons. Besides, the SD N Mulyoharjo 01 Jepara've never apply learning by using themes or thematic learning in students. To improve the learning outcomes of this environmental theme used instructional media Tree Couple. In the process of learning to use media Tree Couple pemikirannyasecara students can train quickly and precisely.The study was aimed to determine students' mastery learning on environmental themes. The purpose of this study was to determine the effectiveness of media Tree Couple itself.This type of research is quantitative. The population in this study were all students of class II SD N Mulyoharjo 01 Jepara. The sample in this study amounted to 79 students with a saturated sampling technique and design research is pretest-posttest control design.Based on the analysis of research data that has been implemented is obtained t = 3.779 and t table = 1.667 so thitung> ttabel then Ho is rejected. the students who completed the experimental class were 36 students and control class is 20 students. This may imply that the media Tree Couple learning can improve student learning outcomes environmental themes.The conclusion that can be drawn from this study is that the results of student learning theme of the environment by using instructional media Tree Couple more effective and can achieve mastery learning students. Suggestions submitted that teachers should use instructional media Tree Couple because it is more effective and able to achieve mastery learning students.